Integrated learning of Chyngyz Aitmatovs worj with uzbek literature (Journal of Educational Sciences, 2017)
In this article we are talking about integrated education of Kyrgyz literature with Uzbek literature in schools of Kyrgyzstan teaching language in Uzbek. Studying the same program of Chyngyz Aitmatov in Kyrgyz, and Uzbek literature, students can lose time. Therefore, the integrated lesson allows you to save time for a more complete discussion of the studied works. From the methodological point of view the advantages of integration of subjects, allows students to experience the world as a whole, to analyze and synthesize theinformation. For teachers integrated lessons allow to associate the content of the material being studied in two or more subjects, teachers and students free from the inertia of traditional lessons. While integrating Kyrgyz literature with Uzbek literature it is important to acquaint the students with information on the Kyrgyz-Uzbek literature connections. This article contains information about Uzbek translators of Chingiz Aitmatov works such as A.Rashidov, S.Karaev, G.Ibraimov, M.Mahmudov. On the integrated lessons it is also important to pay attention to the topics, to the idea of works and literature heros in the Kyrgyz and Uzbek literature, which are common to both the Kyrgyz and the Uzbek people.
Keywords: integration; interdisciplinary connection; academic discipline; academic programme; textbook; literary conceptions of students; competent evaluation; aesthetic taste; forming good breeding